Sistem Informasi Inventory Barang Menggunakan Metode Fifo Pada Pt. Exelindo Bintan Sahtera Tanjungpinang - Ricak Agus Setiawan; Shelvy Sofiana; Titania Pricillia (Jurnal Bangkit Indonesia, 2018)
With the development of the times, the more sophisticated world of technology. All information that we want can be obtained easily. Internet access is getting faster and the software world is progressing very rapidly. This progress must be based on balanced advances in technology, one of which is by producing reliable programmers. PT Exelindo has quite rapid activities, from ordering, importing goods to releasing goods. Stock processing for now is still manual, so the owner does not know the old stock that is still available. Therefore, an application is made that can help the owner and his employees in processing the data, as well as the number of items available. Tools that are used as assistive tools in this research are using Netbeans Tools and Database management Using MySQL Systems.